1975
DOI: 10.1016/0165-1110(75)90002-0
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyurea

Abstract: Hydroxyurea (HU) is an anti-leukaemia and anti-tumour drug which has also found limited application in the treatment of dermatological disorders. It is a potent inhibitor of DNA synthesis in many organisms from viruses to man and in cell culture systems. To a lesser degree it can also inhibit RNA and protein synthesis. It is anti-mitotic and cytotoxic depending on the concentration used, the duration of exposure, and the sensitivity of the organism. In most cells HU is active mainly in the S-phase of the cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
112
0

Year Published

1977
1977
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 238 publications
(113 citation statements)
references
References 76 publications
1
112
0
Order By: Relevance
“…A deletion event, produced by "slippage" of the nascent strand on its template, gives rise to lacZ reversion. diphosphates to deoxynucleotide diphosphates, thereby depleting precursor pools for DNA synthesis (Timson 1975). We used sublethal doses of HU during expansion of the cultures and measured Lac 1 reversion rates in the deletion and QP5 reporters, as well as a transition mutation (AT to GC) and a frameshift (11G) reporter.…”
Section: Resultsmentioning
confidence: 99%
“…A deletion event, produced by "slippage" of the nascent strand on its template, gives rise to lacZ reversion. diphosphates to deoxynucleotide diphosphates, thereby depleting precursor pools for DNA synthesis (Timson 1975). We used sublethal doses of HU during expansion of the cultures and measured Lac 1 reversion rates in the deletion and QP5 reporters, as well as a transition mutation (AT to GC) and a frameshift (11G) reporter.…”
Section: Resultsmentioning
confidence: 99%
“…It is difficult to calculate the exact amount of hydroxyurea administered but the ingested quantity was probably in the range of 0.3-3 mg/g, based on the average worker body weight and estimated food consumption. Hydroxyurea has a general cytostatic effect well below these concentrations (Timson, 1975) and the resistance of the honeybee intestinal stem cells therefore seems remarkable. The significant, repeatable treatment effect on survival provides independent confirmation that the dose used was biologically active.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, asynchronously growing HeLa1 cells can be an appropriate source for isolating unduplicated centrosomes. It has been shown that when exposed to DNA synthesis, inhibitors such as hydroxyurea (HU; an inhibitor of ribonucleotide reductase (Timson, 1975)), majority of the unduplicated centrosomes complete duplication, yet further duplication (re-duplication) of duplicated centrosomes is suppressed in the presence of p53 (Tarapore and Fukasawa, 2002). Because HeLa1 cells contain functional p53, most unduplicated centrosomes complete duplication, but further duplication is suppressed during HU-induced arrest.…”
Section: Characterization Of Centrosomal Localization Of Mortalinmentioning
confidence: 99%